2013
DOI: 10.4041/kjod.2013.43.2.101
|View full text |Cite
|
Sign up to set email alerts
|

Combined treatment with headgear and the Frog appliance for maxillary molar distalization: a randomized controlled trial

Abstract: ObjectiveTo evaluate the efficiency of the Frog appliance (FA) alone or in combination with headgear for distalizing the maxillary molars.MethodsFifty patients (25 males and 25 females) aged 12.6 - 16.7 years who received treatment for Class II malocclusion at the Orthodontic Clinic of Al-Baath University were selected for this study and randomly divided into 2 equal groups. Maxillary molar distalization was achieved using the FA alone (group 1) or a combination of the FA with high-pull headgear worn at night … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 18 publications
1
22
1
2
Order By: Relevance
“…Previous studies showed 6.4 and 3.9 mm of first molar distalization using TAD-anchored appliances, with distal tipping of 10.9u and 8.8u, respectively. 13,14 Meanwhile, Burhan 29 showed 5.5 mm of molar distalization, 4.9u of distal tipping, and 2.7 mm loss of anchorage with a Frog appliance; however, when combined with headgear, the values were 5.9 mm, 1.25u, and 0.9 mm, respectively, which increased bodily distalization with less anchorage loss.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed 6.4 and 3.9 mm of first molar distalization using TAD-anchored appliances, with distal tipping of 10.9u and 8.8u, respectively. 13,14 Meanwhile, Burhan 29 showed 5.5 mm of molar distalization, 4.9u of distal tipping, and 2.7 mm loss of anchorage with a Frog appliance; however, when combined with headgear, the values were 5.9 mm, 1.25u, and 0.9 mm, respectively, which increased bodily distalization with less anchorage loss.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the combination of the 2 modalities has been reported. 12 Although this decreased the unfavorable effects of the intraoral appliances, it still depended on the patient's cooperation. Several authors have reported the application of temporary skeletal anchorage devices to distalize the maxillary posterior teeth.…”
Section: Discussionmentioning
confidence: 99%
“…Ağız içi molar distalizasyonu yöntemlerinin, ağız dışı yöntemlere göre kullanımlarının daha rahat ve kolay olması, estetik açıdan daha kabul edilebilir olmaları ve devamlı kuvvet uyguladıkları için tedavi süresi-nin kısa olması gibi bazı avantajlara sahip olsa da anKraj kaybı, molar tipingi ve ekstrüzyonu sonucu oluşan bite açılması ve overjette artış gibi yan etkilere sahiptir 19 . Son yıllarda, ağız içi molar distalizasyonu yöntemlerinin avantajlarına sahip olduğu, ama dezavantajlarını taşımadığı düşünülerek ortodontik tedavilerde ankraj amacıyla implant ve mini plaklar yaygın olarak kullanılmaya başlanmıştır 11 .…”
Section: Discussionunclassified